Changes In Physical and Chemical Properties of Peat In Various Ages of Oil Palm Plant In East Kotawaringin District - Rahmawati, Reni; Penyang, Penyang; K. Firdara, Eritha; T, Yusintha; Rosdiana, Rosdiana; E. Putir, Patricia (Green Publisher Indonesia, 2022)
The purpose of this study was to examine changes in the physical and chemical properties of natural peat forests and peatlands designated for oil palm plantations at various ages of oil palm planting. The research was carried out in 4 (four) locations in East Kotawaringin Regency, namely: (1) Natural peat swamp forest in Kota Besi District (2) Peat land designated for oil palm plantations planting age less than 4 years in Parenggean District; (3) Peat land designated for oil palm plantations with a planting age of 4-10 years in Cempaga District; and (4) peat land designated for oil palm plantations with a planting age of more than 10 years in Mentawa Baru District, Ketapang. The results showed that the peat land designated for oil palm plantations caused changes in the physical and chemical properties of the peat soil. Changes in the physical properties of peat soil are indicated by the color of the peat soil which changes from very dull red in natural peat forests to reddish black in oil palm plantations. Peat maturity changes from fibric in natural peat forest to hemic and sapric on peatland designated for oil palm plantations. The water content has decreased significantly, the older the age of the oil palm plant, the water content will decrease. In terms of bulk density, the older the age of oil palm plantations, the higher the density of peat soils. The water level in oil palm plantations has increased when compared to natural peat forests. Changes in chemical properties were indicated by an increase in peat soil pH, total N, and available P, while a decrease occurred in the C-Organic content. An increase also occurred in the content of K-dd, Ca-dd, Mg-dd, Na-dd, and CEC with increasing age of oil palm plants. When viewed from the relationship pattern of each physical characteristic, water content has a positive relationship with fiber content, the higher the water content will be followed by the higher fiber content or vice versa. Bulk density has a negative relationship with fiber content and moisture content, which means that an increase in the bulk density of peat soil will be followed by a decrease in fiber content and moisture content. The relationship pattern of chemical properties shows that the pH (H2O) of peat soil has a positive relationship with organic C, total N, available P, and Cation Exchange Capacity (CEC). High or low peat acidity will be proportional to the high or low -organic, N-total, P-available, and Cation Exchange Capacity (CEC).